Analysis of Bank Soundness Level with CAMEL Method at Bank Syariah Indonesia Tbk in 2021 - Dina Nurmalita Sari; Nadila Maulina; Ahmad Fauzul Hakim Hasibuan (Jurma : Jurnal Program Mahasiswa Kreatif, 2022)
BSI is the largest Islamic bank in Indonesia as a result of the merger of three Islamic banks from the Association of State-Owned Banks (Himbara), namely: PT Bank BRI Syariah (BRIS), PT Bank Syariah Mandiri (BSM), and PT Bank BNI Syariah (BNIS). The purpose of the merger of Islamic banks is to encourage larger Islamic banks so that they can enter the global market and become a catalyst for Islamic economic growth in Indonesia. Bank Indonesia as the authority has issued a regulation regarding the assessment of the soundness of banks through a circular letter of Bank Indonesia April 30, 2004 using the CAMEL method, using financial ratios. The object of this research is the Indonesian Islamic Bank for the 2021 period. The purpose of this study is to assess the soundness of the Indonesian Islamic Bank for the 2021 period using the CAMEL method. Bank Syariah Indonesia is expected to become an accelerator for the development of the Islamic economy in Indonesia. The results of the study show that Bank Syariah Indonesia in 2021 will get a healthy predicate.